Water quality for agricultural use of Mololoa river, Mexico - Ortiz Vega, Moisés Ignacio; Can Chulim, Álvaro; Romero Bañuelos, Carlos Alberto; Cruz Crespo, Elia; Madueño Molina, Alberto (REVISTA TERRA LATINOAMERICANA, 2019)
Wastewater discharge from urban, industrial and agricultural sources is the main cause of degradation of river water quality. Water from the Mololoa river is used for irrigation and receives discharges of wastewater from several towns and a greater volume from the city of Tepic. In order to evaluate the quality of the river water for agricultural use, 12 sampling sites were established along the river channel. Sampling was monthly from January to December 2016. Water quality was classif ied by pH, EC, ES, SAR and RSC. During the entire sampling period pH was alkaline, with an average of 7.5, minimum 6.3 and maximum 8.9, and EC was on average 304, minimum 139 and maximum 831 μS cm-1. Of the samples, 50.7% were classif ied as C1, 48.6% C2 and 0.7% C3. With the ES, 131 samples were classif ied as very good to good quality, eight as good to dangerous and one as dangerous to very dangerous. SAR values were on average 1.6, minimum 0.3 and maximum 4.4. RSC indicates that 97% of the samples are of good quality for agricultural use and 3% conditioned. In the dry season pH was alkaline with an average of 7.7, minimum 6.3 and maximum 8.9; in the rainy season it was neutral with an average of 7.3, minimum 6.5 and maximum 7.8. An increase in pH, EC, ES, SAR and RSC was obtained in the dry season, and the highest values were found in May at the La Escondida site, where all the wastewater discharges from the city of Tepic and the El Iztete landf ill are concentrated. The water of the Mololoa river at the La Escondida site is not recommended for irrigation in the month of May.